Sintering Techniques of Materials - Lakshmanan, Arunachalam (IntechOpen, 2015)
The book covers new sintering techniques on ceramic materials, metals and composites as well as reprocessed PTFE. The book covers theoretical as well as experimental aspects on Spark Plasma Sintered (SPS) Porous copper, development of cutting blades with high hardness and resistance to cracking and wear, increased microhardness of austenitic steel ? TiB2 composites obtained with high pressure - high temperature sintering, Al2O3 porous body with cotton as the template and excellent thermal insulation with direct application for refractories as well as Metal matrix composites added nanostructured tantalum carbide and an overview of different sintering techniques used in powder metallurgy. Finally recycling of PTFE scrap materials using ram extrusion and compression molding is described.